Enhancing Confidence In Brain Tumor Classification Models With Grad-CAM And Grad-CAM++ - Vo, Hoang-Tu Vo; Thien, Nhon Nguyen; Mui, Kheo Chau; Tien, Phuc Pham (IAES Indonesian Section, 2024)
Brain tumors are a terrible and dangerous health problem, often posing a significant threat to individuals due to their high probability of death. Detecting these tumors at an early stage is crucial, as it not only increases the chances of successful treatment but also plays a pivotal role in reducing total healthcare costs. Early detection allows medical professionals to take action quickly, enabling a more targeted and effective treatment approach. Numerous studies are currently employing Machine Learning (ML) and Deep Learning (DL) to classify brain tumors, promising improved accuracy and efficiency in tumor identification for potential breakthroughs in medical diagnosis. However, a significant challenge lies in these models being